The Womanhood of Roko Molas Poco Rite in Manggarai's Patriarchal Culture: A Discourse on Simone de Beauvoir - Letsoin, Yetva Softiming; Sembiring, Kristinus; Suhartini, Yosefina Elsiana (Perspektif, 2024)
This paper focuses on exploring the role of women in the Roko Molas Poco rite in Manggarai. This study applies a discourse approach by referring to Simone de Beauvoir's concept of feminism. She views women as "the Other," often an object in a patriarchal society. The patriarchal system adopted by the Manggaraians is deeply rooted and thus influences the treatment of women. Femininity has a very important meaning in this rite, because the wood called siri bongkok (main pole) is symbolized as virgin who will provide life, offspring, fertility for humans. It’s a symbol that connects humans with nature and humans with each other and humans with the Supreme Being. This rite in itself affirms the high appreciation for the existence of women as Simone de Beaouvoir. The concept of womanhood in the Roko Molas Poco rite is a living critique of the patriarchal system that oppresses and otherizes women.